Active self-motion control and the role of agency under ambiguity - Rineau, Anne-Laure; Berberian, Bruno; Sarrazin, Jean-Christophe; Bringoux, Lionel (Frontiers in Psychology, 2023)
Self-motion perception is a key factor in daily behaviours such as driving a car or piloting an aircraft. It is mainly based on visuo-vestibular integration, whose weighting mechanisms are modulated by the reliability properties of sensory inputs. Recently, it has been shown that the internal state of the operator can also modulate multisensory integration and may sharpen the representation of relevant inputs. In line with the concept of agency, it thus appears relevant to evaluate the impact of being in control of our own action on self-motion perception. Here, we tested two conditions of motion control (active/manual trigger versus passive/observer condition), asking participants to discriminate between two consecutive longitudinal movements by identifying the larger displacement (displacement of higher intensity). We also tested motion discrimination under two levels of ambiguity by applying acceleration ratios that differed from our two “standard” displacements (i.e., 3 sec; 0.012 m.s-2 and 0.030 m.s-2 ). We found an effect of control condition, but not of the level of ambiguity on the way participants perceived the standard displacement, i.e. perceptual bias (Point of Subjective Equality; PSE). Also, we found a significant effect of interaction between the active condition and the level of ambiguity on the ability to discriminate between displacements, i.e. sensitivity (Just Noticeable Difference; JND). Being in control of our own motion through a manual intentional trigger of self-displacement maintains overall motion sensitivity when ambiguity increases.